TECHNOLOGY OF ORGANIZING LEISURE OF DIFFICULT CHILDREN (Education in the 21st Century, 2023)
When selecting the technologies for organizing leisure activities, one should take into account the basic conditions and factors of socialization of difficult children, their individual, as well as national characteristics. It is important to emphasize that leisure activities are a continuation of work or study activities. In fact, the successful organization of children's leisure activities is a prerequisite for the effective organization of their labor activity. In the educational process, teachers use different technologies for organizing leisure activities for difficult children. It is very difficult to assess the effectiveness of the technologies used, since the implementation of an objective assessment must take into account the main educational, extracurricular factors, develop appropriate assessment criteria, and properly develop reflexive competence. Very often, teachers, having clear ideas about the technologies of organizing leisure activities, about physical exercises, outdoor folk games and sport games are not able to use this knowledge at the proper level.The technologies for organizing leisure activities for difficult children should contain elements of ceremonial, ritual, fortune-telling, and, in general, folk games. When selecting entertaining games, it is also necessary to take into account the individual and national characteristics of difficult teenagers.All types of leisure activities, physical education, folk and other types of games, if they are organized correctly and on time, can positively influence the process of socialization of difficult children.109Extracurricular physical education classes are of great importance in the process of using innovative technologies to organize leisure activities of difficult children, preventing their asocial behavior.